2017
DOI: 10.1002/ajmg.a.38538
|View full text |Cite
|
Sign up to set email alerts
|

Kaufman oculocerebrofacial syndrome: Novel UBE3B mutations and clinical features in four unrelated patients

Abstract: The "blepharophimosis-mental retardation" syndromes (BMRS) consist of a group of clinically and genetically heterogeneous congenital malformation syndromes, where short palpebral fissures and intellectual disability associate with a distinct set of other morphological features. Kaufman oculocerebrofacial syndrome represents a rare and recently reevaluated entity within the BMR syndromes and is caused by biallelic mutations of UBE3B. Affected individuals typically show microcephaly, impaired somatic growth, gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
(63 reference statements)
4
19
0
Order By: Relevance
“…In the current study, all our patients were found to harbor homozygous variants in the UBE3B gene. Five different variants were iden- the UBE3B gene were associated with a severe phenotype (Basel-Vanagaite et al, 2012, 2014Flex et al, 2013;Galarreta et al, 2019;Kariminejad et al, 2017;Pedurupillay et al, 2015;Yilmaz et al, 2018). This is in accordance with the phenotypic severity observed in our patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the current study, all our patients were found to harbor homozygous variants in the UBE3B gene. Five different variants were iden- the UBE3B gene were associated with a severe phenotype (Basel-Vanagaite et al, 2012, 2014Flex et al, 2013;Galarreta et al, 2019;Kariminejad et al, 2017;Pedurupillay et al, 2015;Yilmaz et al, 2018). This is in accordance with the phenotypic severity observed in our patients.…”
Section: Discussionsupporting
confidence: 90%
“…The most characteristic facial dysmorphic features of BPID were striking in the present patients including blepharophimosis, ptosis, sparse arched laterally broad eyebrows, epicanthic folds, sparse hair, long face, frontal bossing, short broad nose, and ear abnormalities. Further, hypotonia and microcephaly were recorded in most of them as previously reported(Basel- Vanagaite et al, 2012;Galarreta et al, 2019;Yilmaz et al, 2018). The constellation of facial dysmorphic features become more pronounced with age specifically the eyebrows, upslanting of palpebral fissures, and face elongates, which were also identified in our older patients (Patients 3, 4, and 9)(Galarreta et al, 2019).Long slender phalanges have been reported and were present in all studied patients (Basel-Vanagaite et al, 2014).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…In addition, HECTD2 polymorphisms have been shown to be associated with an increased risk of prion infections, including Creutzfeldt-Jakob disease and kuru (Lloyd et al, 2009). Moreover, mutations in UBE3B gene have been correlated with the development of Kaufman oculocerebrofacial syndrome (KOS), a rare autosomal recessive neurodevelopmental disorder (Flex et al, 2013;Pedurupillay et al, 2015;Yilmaz et al, 2018).…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%